Reliable Temperature Measurement in Radiation-Intensive Environments - Petrashin, Pablo; Lancioni, Walter; Laprovitta, Agustin; Castagnola, Juan (JAREE (Journal on Advanced Research in Electrical Engineering), 2024)
Radiation-resistant temperature sensors are vital for ensuring reliability in radiation-intensive environments, where the highly energetic and penetrating nature of radiation can significantly impact electronic devices and sensors. In such environments, like those near intense radiation sources or in challenging radiation-rich settings, such as space, gamma radiation can lead to erroneous measurements or equipment failures. Radiation-resistant sensors play a crucial role in maintaining measurement accuracy as they are designed to minimize interference caused by radiation, protecting electronic components and providing precise and reliable temperature readings. Their resilience to radiation-induced effects ensures data durability, reducing the need for frequent replacements, and enhancing the overall reliability of measurements in these demanding conditions. In this paper, we present and analyze two different configurations, aiming to address the challenges posed by radiation in sensitive environments. By exploring these novel approaches, we seek to enhance the robustness and accuracy of temperature sensors in radiation-intensive settings, enabling reliable data collection and facilitating successful operations in challenging radiation-rich conditions. The comparative analysis of these configurations will shed light on their performance and effectiveness in mitigating radiation-induced effects, thereby contributing to the advancement of radiation-resistant temperature sensing technologies.